Evidence from Cochrane systematic reviews for effects of antithrombotic drugs for lower-limb revascularization. A narrative review - Dias, Silfayner Victor Mathias (2021)
BACKGROUND: Peripheral arterial disease (PAD) is characterized by progressive narrowing of the arterial lumen, resulting from atherosclerotic plaques. Treatment for PAD aims to control atherosclerosis and improve blood flow. Use of antiplatelet agents and anticoagulants has played important roles in helping to prevent occlusions and stenosis. OBJECTIVE: To evaluate the evidence from Cochrane systematic reviews regarding the accuracy, effectiveness and safety of use of anticoagulants and antiplatelets in lower-limb revascularization, in patients with peripheral arterial disease. METHODS: Systematic reviews found through searches in the Cochrane Library were included. Two authors evaluated whether the reviews found were in line with the inclusion criteria for this investigation. A qualitative synthesis of their findings was presented. RESULTS: Three systematic Cochrane reviews were included. Patients who underwent prosthetic bypass surgery probably presented greater benefit from use of antiplatelets, and patients who underwent vein revascularization probably presented greater benefit from use of anticoagulants. Patients who received endovascular treatment benefited from both antiplatelet and anticoagulant treatment. However, the reliability of the results found was impaired because at the time when these reviews were published, there was no mandatory assessment using the GRADE criteria. CONCLUSION: Despite the evidence found, it is necessary for these reviews to be updated in order to evaluate the degree of certainty of the results found.